Development of multivalent nanobodies blocking SARS-CoV-2 infection by targeting RBD of spike protein - Qizhong Lu (Journal of Nanobiotechnology, 2021)
Abstract Background The outbreak and pandemic of coronavirus SARS-CoV-2 caused significant threaten to global public health and economic consequences. It is extremely urgent that global people must take actions to develop safe and effective preventions and therapeutics. Nanobodies, which are derived from single‑chain camelid antibodies, had shown antiviral properties in various challenge viruses. In this study, multivalent nanobodies with high affinity blocking SARS-CoV-2 spike interaction with ACE2 protein were developed. Results Totally, four specific nanobodies against spike protein and its RBD domain were screened from a naïve VHH library. Among them, Nb91-hFc and Nb3-hFc demonstrated antiviral activity by neutralizing spike pseudotyped viruses in vitro. Subsequently, multivalent nanobodies were constructed to improve the neutralizing capacity. As a result, heterodimer nanobody Nb91-Nb3-hFc exhibited the strongest RBD-binding affinity and neutralizing ability against SARS-CoV-2 pseudoviruses with an IC50 value at approximately 1.54 nM. Conclusions The present study indicated that naïve VHH library could be used as a potential resource for rapid acquisition and exploitation of antiviral nanobodies. Heterodimer nanobody Nb91-Nb3-hFc may serve as a potential therapeutic agent for the treatment of COVID-19.